2006
DOI: 10.1159/000092475
|View full text |Cite
|
Sign up to set email alerts
|

Nanobacteria, HIV and Magic Bullets – Update of Perspectives 2005

Abstract: In 1997 a Finnish group speculated on the presence of nanobacteria in vaccines. In 2001, a report on the identification of nanobacteria in a number of vaccines attracted much attention. Experiments indicated that viable nanobacteria are excreted via urine. Their extreme survivability suggests that prior to discussing any possible contamination of vaccines, sources and routes of natural infection need to be examined. In view of 30,000,000 HIV infections in sub-Saharan Africa, the recently reported occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…They are thought to react with a bacterial porin-like protein synthesized by these nanoentities (3). Surprisingly, experiments attempting to identify the exact nature of this antigenic reactivity have never been reported, and yet the same antibodies were used in past studies to affirm the presence of nanobacteria (3,5,7). We first observed that antibody 8D10 reacted with NLP obtained after pelleting the material from 1-month-old culture (Fig.…”
Section: Nanobacteria-specific Antibodies React With Human Serum Albuminmentioning
confidence: 92%
“…They are thought to react with a bacterial porin-like protein synthesized by these nanoentities (3). Surprisingly, experiments attempting to identify the exact nature of this antigenic reactivity have never been reported, and yet the same antibodies were used in past studies to affirm the presence of nanobacteria (3,5,7). We first observed that antibody 8D10 reacted with NLP obtained after pelleting the material from 1-month-old culture (Fig.…”
Section: Nanobacteria-specific Antibodies React With Human Serum Albuminmentioning
confidence: 92%
“…Our interest in NPs was triggered by a vast amount of literature surrounding the so-called primitive life-forms known as nanobacteria (NB) that have been described as the smallest living symbionts on earth [15]–[22], with claimed implications for a number of disease processes that include Alzheimer’s disease [23], atherosclerosis [24], calciphylaxis [25], cancer [26][28], co-infection with HIV [29], ectopic calcification [22], [24], [30][37], male infertility [38], periodontal disease [39], polycystic kidney disease [40], prostatitis [41], [42], arthritis [43], [44], and renal stone formation [17][21], [45], [46]. NB have also been implicated as potential worldwide airborne pathogens [47], as potential contaminants in vaccines [48], and as infectious agents of disease transmissible through intravenous injection and other forms of inoculation [34].…”
Section: Introductionmentioning
confidence: 99%
“…As agents of transmissible infectivity, NB are said to fulfill either in part or completely the classic Koch's postulates [6][8], [28], [36]–[39]. On these same grounds, NB have been proposed as a potential global health hazard [16], [17], [40], [41]. NB are thus unusual in that they are seen by some [25] not only as primitive symbionts and precursors of biological life but also as infectious agents of disease—extraordinary claims in themselves that have led to intense debate and skepticism.…”
Section: Introductionmentioning
confidence: 99%